Cells the building blocks of life - Mindham, James (Jaguar Educational, 2001)
All living things, from bacteria to plants and animals, are made up of the same basic microscopic building blocks, called cells. Although there are different types of cells for different specific functions, they have many features in common. This video uses microscope imaging and 3-D animation techniques to illustrate the cellular processes associated with being alive: eating, drinking, breathing and growing.